Environmental Education and Primary School Curriculum: A Missing Link. - Ashabahebwa, James (Kabale University, 2024)
This study explored the gaps between environmental education and its implementation within Uganda's primary school curriculum. It focused on three primary objectives: assessing the extent of environmental education integration, identifying challenges faced by educators and learners, and proposing strategies for improved incorporation. Using a mixed-methods approach, the research combined quantitative surveys and qualitative interviews, collecting data from primary school teachers, curriculum planners, and education policymakers in Rubanda District. The findings revealed that while environmental education is included in the curriculum, its integration is inconsistent, with some schools reporting minimal or no implementation. Major challenges highlighted include insufficient training for educators, inadequate resources, and a lack of administrative support. Proposed strategies to address these issues involve increasing funding for educational materials, enhancing teacher training, and developing specialized curriculum guides. In conclusion, the study recognized a foundational presence of environmental education in Ugandan primary schools but emphasized the need for significant enhancements. Recommendations include investing in professional development for teachers, allocating more financial resources for educational tools, creating detailed curriculum guides, and strengthening administrative backing. Additionally, incorporating hands-on learning experiences and revising the curriculum to achieve a balanced integration of environmental education are critical for fostering its effective implementation.